A 1994 Social Accounting Matrix (SAM) for Peru - International Food Policy Research Institute (International Food Policy Research Institute, 2005)
The 1994 Social Accounting Matrix (SAM) for Peru was assembled as part of a project aimed at analyzing the distributive effects of trade liberalization in a general-equilibrium context. The SAM disaggregates the production activities, labor and households accounts, and opens up the possibility to engage in a detailed analysis of the productive structure of the economy, as well as of the income distribution channels. The accompanying documentation describes both, the macroeconomic and microeconomic SAMs, paying special attention to data sources, assumptions, and balancing procedures.